SUSTAINABLE DEVELOPMENT DIRECTIONS OF RURAL TOURISM OF TIMOK REGION - Ilić, Biljana; Djukić, Gordana; Balaban, Mladenka (Economics of Agriculture, 2020)
In Eastern Serbia in the Timok Region, the cult of household hospitality is still fostered. The Timok region belongs to the underdeveloped parts of Serbia and starting from the fact that the growth of local economy capacity also leads to overall regional development, the development of rural tourism could contribute to the well-being of the region. The paper examines sustainable development directions of rural tourism, taking into account the economic, environmental and social components, which are elements of sustainability. The authors apply Multi-CriteriaDecision-Making methods, ELECTRE as main, and AHP as an auxiliary method in the selection of an adequate and optimal solution. The aim of the paper is choosing the optimal projects for the development of rural tourism in the Timok region, based on well-defined criteria, among the several proposed projects.